Platinum-based packaging mesoporous titanium oxide electrocatalyst and preparation method and application thereof
Defective mesoporous titanium dioxide microspheres encapsulated with Pt were synthesized by solution evaporation-induced single micelle self-assembly, which solved the problems of resource scarcity and stability of Pt-based catalysts and achieved highly efficient electrocatalytic water splitting performance, especially the stability and activity under acidic conditions.
Patent Information
- Application Number
- CN202511420782.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-09-30
AI Technical Summary
Existing Pt-based catalysts for electrocatalytic water splitting suffer from resource scarcity, high cost, and poor long-term cycle stability. Furthermore, the ultrafine nanostructures are prone to irreversible structural changes under reaction conditions, leading to a decrease in catalytic activity and limiting their catalytic activity on an industrial scale.
Using nonionic surfactants as structure directing agents, defective mesoporous titanium dioxide microspheres encapsulating Pt were synthesized via solution evaporation-induced single micelle self-assembly. By utilizing strong metal-support interactions, ultrafine Pt nanostructures were loaded to form a high-performance electrocatalyst.
It improves the stability and activity of the catalyst, exhibits excellent catalytic performance in acidic electrocatalytic water splitting cathodes, and can be used stably for a long time in highly corrosive environments, with high specific surface area and high charge transport efficiency.
Smart Images

Figure CN120888965A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of energy material design and synthesis, and particularly relates to a platinum-based encapsulated mesoporous titanium oxide electrocatalyst, a preparation method and application thereof. BACKGROUND
[0002] The energy crisis caused by the continuous consumption of fossil fuels and a series of problems such as global warming have become the focus of the world. The growing demand for fossil fuels and their non-renewable nature have made the energy crisis problem increasingly serious. The demand for renewable energy that can be combined with power generation systems is more urgent than ever. For this reason, researchers are constantly exploring methods for developing and applying renewable energy such as hydroelectric power and wind energy. However, due to the temporal and spatial discontinuity of these renewable energy sources, the energy transmission efficiency is low. Therefore, there is an urgent need to develop energy storage technologies associated therewith.
[0003] Among the many energy carriers, hydrogen is an ideal energy carrier with extremely high energy density, and its use is of great significance in solving energy crisis and environmental problems. Among many methods for producing hydrogen, electrocatalytic water splitting for hydrogen production represents the most scalable technology, which has the characteristics of environmental protection, high efficiency, controllability, etc., and is a key strategy for producing green hydrogen. This technology can use renewable energy such as solar energy and wind energy to decompose water into hydrogen and oxygen, thereby obtaining hydrogen with high energy density, no pollution, easy storage and transportation to meet the growing energy needs of people, and at the same time, producing "green hydrogen" from renewable resources will greatly reduce the environmental problems caused by the emission of carbon-based substances. However, the hydrogen generation efficiency of this method is still limited. This limitation is caused by the slow kinetics of the two half-reactions of the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER) in the process of electrolytic water hydrogen production.
[0004] The key to overcoming this slow kinetics is to develop advanced electrocatalysts for electrocatalytic water splitting. By accelerating the reaction process through electrocatalysts, the additional energy required for the reaction is reduced to achieve an electrolytic water process that is closest to the ideal state. So far, Pt-based catalyst materials are still considered the best choice for HER catalysts due to their optimal hydrogen binding energy. However, they face problems such as resource scarcity, high price, and poor long-term cycle stability, which limit the practical application of Pt-based catalyst materials in the field of electrocatalytic water splitting.
[0005] Therefore, two approaches have been proposed by many researchers, one is to find substitutes, such as a large number of non-noble metal-based electrocatalysts with high stability synthesized by modification design, however, the performance of non-noble metal-based catalysts in practical application still cannot compare with that of Pt-based catalysts. The second is to improve the utilization efficiency, such as ultrafine Pt nanostructures, including single atoms (SAs), sub-nanoclusters (SNCs) and nanoparticles, aiming to greatly improve the catalytic activity and maximize the utilization efficiency of precious Pt. Ultrafine nanostructures have unique electronic structures, geometric characteristics, tunable coordination environments and high atomic utilization efficiency. However, ultrafine nanostructures often undergo irreversible structural changes, such as dissolution, Ostwald ripening and agglomeration, due to their high surface free energy under reaction conditions. This leads to a cliff-like decline in performance. And in practical applications, the catalytic activity of Pt-based catalysts at the current density of industrial scale is fundamentally limited, in which excessive bubble generation hinders the effective transfer of electrolyte to active sites.
[0006] Among the many strategies being studied, strong metal-support interaction (SMSI), especially through the encapsulation of metal nanostructures to improve catalyst stability, has attracted great attention. Among various support materials, mesoporous materials, especially mesoporous titanium dioxide (TiO2), show great potential as ideal supports for high-performance electrocatalysts due to their large specific surface area, richly tunable pore structure, natural abundance and excellent corrosion resistance. In recent years, a soft template method based on solution evaporation-induced micellar self-assembly has been developed to synthesize mesoporous titanium dioxide. Based on this method, a large number of various mesoporous titanium dioxide have been synthesized. By loading ultrafine Pt nanostructures on mesoporous titanium dioxide as a support through strong metal-support interaction, the stability of the material can be greatly improved while ensuring the high activity of Pt as an active site, which has guiding significance for developing electrocatalysts with high activity and high stability. SUMMARY
[0007] To solve the problems of the prior art, the present application provides a preparation method of a platinum-based encapsulated mesoporous titanium oxide electrocatalyst.
[0008] The specific technical solutions of the present application are as follows:
[0009] A preparation method of a platinum-based encapsulated mesoporous titanium oxide electrocatalyst, characterized in that a non-ionic surfactant is dissolved in an organic solvent, and stirring is continued until dissolution; hydrochloric acid and acetic acid are added to the mixed solution, and stirring is continued until mixing is uniform, and then an organic compound is added, and stirring is continued until dissolution; finally, metal salt and an organic compound are added to the mixed solution, and stirring is continued to obtain a precursor solution. At a certain temperature, the organic solvent is preferentially evaporated to form a composite soft micelle hydrogel. The composite soft micelle hydrogel is added to a hydrothermal reactor, and hydrothermal treatment is performed, and a low-crystalline platinum-based encapsulated mesoporous titanium oxide microsphere is obtained. The low-crystalline platinum-based encapsulated mesoporous titanium oxide microsphere is calcined at high temperature, and a platinum-based encapsulated mesoporous titanium oxide electrocatalyst material is obtained.
[0010] The preparation process method of the platinum-based encapsulated mesoporous titanium oxide electrocatalyst, characterized in that, specifically includes the following steps:
[0011] S1 At room temperature, the non-ionic surfactant is dissolved in the organic solvent, and then acetic acid and hydrochloric acid are added to the solvent as inhibitors for hydrolysis and complexing, and mixed uniformly, and then 2-ethyl imidazole is dissolved in the mixed solution as a defect inducer, and finally platinum metal salt and tetrabutyl titanate are added as metal sources, and stirring is mixed uniformly to obtain an orange clear solution;
[0012] S2 The clear solution is placed at a certain temperature, and the composite micelles formed by the block copolymer and the metal precursor in the solution are self-assembled through the preferential evaporation of the solvent, and after a certain evaporation time, a composite micelle orange hydrogel is formed;
[0013] S3 The above orange gel is added to the Teflon lining of the high-pressure hydrothermal kettle, the high-pressure hydrothermal kettle is sealed, and placed in an electric heating air drying oven for reaction;
[0014] S4 The product obtained after hydrothermal treatment is calcined at a certain temperature in a muffle furnace to remove the template, and a Pt-encapsulated defect mesoporous titanium dioxide microsphere is obtained.
[0015] Further preferably, the organic solvent in step S1 is tetrahydrofuran (THF), and the metal precursor is hydrated platinum chloride (PtCl4·H2O). In step S2, the evaporation temperature is 30-50 °C, and the evaporation time is 20-26 h. In step S3, the hydrothermal temperature is 60-80 °C, and the hydrothermal time is 20-26 h. In step S4, the calcination temperature is 400-450 °C, the temperature rising program is 1-2 °C / min, and the calcination time is 2-4 h.
[0016] Preferably, the non-ionic surfactant is a triblock copolymer, polyethylene glycol-polypropylene glycol-polyethylene glycol, and the triblock copolymer mainly includes Pluronic F127 (EO 106PO 70 EO 106 ), Pluronic P123 (EO 20 PO 70 EO 20 ), and most preferably Pluronic F127 (EO 106 PO 70 EO 106 ).
[0017] A platinum-based encapsulated mesoporous titania electrocatalyst prepared by the above method has a specific surface area of 40-50 m 2 / g and a pore size of 9-12 nm.
[0018] The platinum-based encapsulated mesoporous titania electrocatalyst prepared by the above method is used as a cathode catalyst material for hydrogen production by electrocatalytic water splitting under acidic conditions.
[0019] The platinum-based encapsulated mesoporous titania electrocatalyst prepared by the above method is applied, characterized in that the platinum-based encapsulated mesoporous titania electrocatalyst material is mixed with Nafion solvent and isopropanol solvent to form a catalyst slurry, and the catalyst slurry is drop-coated on a rotating disc electrode, and a three-electrode system is used for electrocatalytic application.
[0020] The platinum-based encapsulated mesoporous titania electrocatalyst prepared by the above method is applied, characterized in that the platinum-based encapsulated mesoporous titania electrocatalyst prepared by the above method is applied, and the application specifically comprises the following steps:
[0021] S1. 4-6 mg of the platinum-based encapsulated mesoporous titania electrocatalyst material is taken as a catalytically active material;
[0022] S2. 5-20 μL of Nafion solvent, 480-500 μL of isopropanol solvent, and the catalytically active material of S1 are taken and physically mixed to prepare a catalyst slurry;
[0023] S3. 5-20 μL of the catalyst slurry is taken and drop-coated on the glassy carbon active surface of a rotating disc electrode, and the slurry is dried to form a film for application;
[0024] S4. The prepared rotating disc electrode is used as a working electrode, an Ag / AgCl electrode is used as a reference electrode, a carbon rod is used as a counter electrode, and a 1.0 M perchloric acid solution is selected as an electrolyte. A three-electrode system is assembled for application of electrocatalytic water splitting for hydrogen production under acidic conditions.
[0025] The application utilizes a soft template self-assembly method of inorganic-organic co-assembly, adopts a solution evaporation induced monomolecular self-assembly synthesis strategy, and controllably synthesizes a Pt encapsulated defective mesoporous titanium dioxide microsphere nanomaterial.
[0026] Compared with the prior art, the application has the following advantages:
[0027] 1. The application utilizes a nonionic surfactant as a structure directing agent, adopts a solution evaporation induced monomolecular self-assembly synthesis strategy, and synthesizes a Pt encapsulated defective mesoporous titanium dioxide microsphere, and the process is simple and convenient to operate, the obtained product has a large specific surface area, a high charge transport efficiency, and many accessible active sites;
[0028] 2. The application encapsulates high-performance particles by using a mesoporous structure with rich channels through strong metal-support interaction, which not only ensures excellent performance of the material, but also ensures long-term stable application of the material;
[0029] 3. The application exhibits excellent catalytic performance in the application of an acidic electrocatalytic water splitting cathode, and can be used stably for a long time in a strong corrosive environment;
[0030] 4. The application has raw materials that are easy to obtain, a simple method, and wide application scenarios in many fields such as energy storage and conversion, catalysis, etc. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 The optical pictures of the Pt encapsulated defective mesoporous titanium dioxide microspheres prepared for Example 1 at each synthesis stage are shown in the following table:
[0032] Figure 2 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the Pt encapsulated defective mesoporous titanium dioxide microspheres prepared for Example 1 are shown in the following table:
[0033] Figure 3 The X-ray diffraction (XRD) spectra of the Pt encapsulated defective mesoporous titanium dioxide microspheres (Pt@DMTO) and titanium dioxide particles (TiO2) prepared for Example 1 are shown in the following table:
[0034] Figure 4 The characteristic nitrogen adsorption-desorption isotherms and pore size distribution curves of the Pt encapsulated defective mesoporous titanium dioxide microspheres (Pt@DMTO) and titanium dioxide particles (TiO2) prepared for Example 1 are shown in the following table:
[0035] Figure 5Linear sweep voltammetry (LSV) plots of Pt@DMTO, DMTO, MTO, P25 and Pt / C as cathode catalysts for electrocatalytic water splitting for hydrogen evolution under acidic conditions;
[0036] Figure 6 Tafel plots of Pt@DMTO, DMTO and Pt / C as cathode catalysts for electrocatalytic water splitting for hydrogen evolution under acidic conditions;
[0037] Figure 7 EIS plots of Pt@DMTO, DMTO, MTO, P25 and Pt / C as cathode catalysts for electrocatalytic water splitting for hydrogen evolution under acidic conditions;
[0038] Figure 8 Stability of LSV plots of Pt@DMTO and Pt / C as cathode catalysts for electrocatalytic water splitting for hydrogen evolution under acidic conditions before and after 10,000 cycles. DETAILED DESCRIPTION
[0039] The application will be described in greater detail with reference to the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the application, and detailed implementation modes and specific operation processes are given, but the protection scope of the application is not limited to the following examples.
[0040] Example 1: Synthesis of Pt-based encapsulated mesoporous titanium oxide electrocatalyst.
[0041] In tetrahydrofuran solvent (30 mL), 1.6 g of triblock copolymer F127, 2.6 mL of acetic acid, 3.2 mL of concentrated hydrochloric acid were added in turn, and a colorless transparent solution was formed under stirring, then 0.5 g of 2-ethyl imidazole was added, stirred to dissolve, finally 0.072 g of PtCl4 and 3 mL of TBOT were added to form an orange transparent solution under stirring for 5 min, then the mixture was transferred to two 15 mL evaporating bottles, and tetrahydrofuran was preferentially evaporated at 40 °C for 24 h to form an orange Pt@F127 / TiO2 composite monomicroemulsion hydrogel. Then the composite monomicroemulsion hydrogel was transferred to a 100 mL Teflon-lined stainless steel autoclave, sealed and reacted at 70 °C for 24 h. After cooling to room temperature, the product in the Teflon liner was collected into a crucible, and then the crucible was placed in a muffle furnace and calcined at 400 °C for 3 h at a heating rate of 1 °C / min under air to obtain Pt-encapsulated defective mesoporous titanium dioxide microspheres (Pt@DMTO). The optical pictures of each stage of synthesis can be seen in Figure 1 . The SEM and TEM pictures are shown in Figure 2 , which can prove that the mesoporous microspheres have good uniformity and radial mesoporous channels diverging from the center, and a large number of Pt single atoms / sub-nanoclusters are loaded on the surface of TiO2 (circled in orange in the figure). Moreover, the XRD comparison chart is shown in Figure 3 , which shows that the original titanium oxide crystal phase has not changed after loading. The nitrogen adsorption-desorption curve and pore size distribution chart are shown in Figure 4 , which proves that the obtained two-dimensional mesoporous titanium dioxide nanosheets have a specific surface area of 46 m 2 / g and a pore size of 11.2 nm.
[0042] Example 2: The platinum-based encapsulated mesoporous titanium oxide electrocatalyst synthesized in Example 1 was applied to the acidic hydrogen evolution reaction.
[0043] Pt@DMTO, 10 μL of Nafion solution and 490 μL of ethanol solution, and ultrasonic treatment for 30 min with constant temperature. Then, 10 μL of the ink was dropped on the working area of a glassy carbon electrode (GCE) and dried at room temperature. The dried GCE was used as the working electrode (WE), a graphite rod as the counter electrode (CE), and a silver / silver chloride (Ag / AgCl) electrode as the reference electrode (RE). The electrolyte was 1.0 M perchloric acid (HCIO4) solution, which was purged with nitrogen for 1 h before use. The above electrode and electrolyte were assembled into a three-electrode electrochemical cell, and electrochemical tests were performed using a Swiss Metrohm Nova N402 electrochemical workstation. Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV s -1 The actual performance results were affected by the solution inter-electrode resistance, and the test results were corrected by iR drop compensation. The iR drop correction amplitude was 90%. After correction, the Pt@DMTO could achieve a low overpotential of 7 mV at a current density of 10 mA cm -2 , which was lower than that of commercial platinum-carbon (Pt / C) and other comparative samples (Pt@MTO, Pt@MTO-2, Pt@MTO-3 and Pt@MTO-4) Figure 5 . In the Tafel slope analysis, the reaction kinetics of Pt@DMTO was better than that of the commercial Pt / C catalyst. Figure 6 Electrochemical impedance spectroscopy (EIS) was performed at a potential of 0.80 V for the reversible hydrogen electrode, and the test frequency range was 0.01 Hz to 100 kHz. The test results were analyzed by fitting with Zview software. The Pt@DMTO had a charge transfer resistance of only 0.68 Ω, which was much smaller than that of the commercial Pt / C Figure 7 . After 10,000 cyclic voltammetry (CV) tests, the linear sweep voltammetry (LSV) before and after the comparative tests was compared. The performance of the Pt@DMTO almost did not decay, and it had excellent stability Figure 8 .
[0044] The above description of the embodiments is to facilitate the understanding and use of the invention by those of ordinary skill in the art. Those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to go through creative labor. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a platinum-based encapsulated mesoporous titania electrocatalyst, characterized by, The non-ionic surfactant is dissolved in an organic solvent, and stirring is continued until dissolution; hydrochloric acid and acetic acid are added to the mixed solution, and stirring is continued until the mixture is uniform; and then an organic compound is added, and stirring is continued until dissolution; Subsequently, a metal salt and an organic compound are added to the mixed solution, and stirring is continued to obtain a precursor solution; the organic solvent is preferentially evaporated at a certain temperature to form a composite soft micelle hydrogel; the composite soft micelle hydrogel is added to a hydrothermal reactor, and hydrothermal treatment is performed, thereby obtaining a low-crystalline platinum-based encapsulated mesoporous titanium dioxide microsphere; and the low-crystalline platinum-based encapsulated mesoporous titanium dioxide microsphere is calcined at high temperature, thereby obtaining a platinum-based encapsulated mesoporous titanium oxide electrocatalyst.
2. The method of claim 1, wherein the platinum-based encapsulated mesoporous titanium oxide electrocatalyst is prepared by the steps of: Specifically comprising the following steps: S1, at room temperature, the non-ionic surfactant is dissolved in an organic solvent, and then acetic acid and hydrochloric acid are added to the solvent as inhibitors of hydrolysis and complexing additives, and mixed uniformly, and then 2-ethyl imidazole is dissolved in the mixed solution as a defect inducer, and finally platinum metal salt and tetrabutyl titanate are added as metal sources, and stirred and mixed uniformly to obtain an orange clear solution; S2, the clear solution is placed at a certain temperature, and the composite micelles formed by the block copolymer and the metal precursor in the solution are self-assembled by the preferential evaporation of the solvent, and after a certain evaporation time, a composite micelle orange hydrogel is formed; S3, the above orange gel is added to the Teflon lining of a high-pressure hydrothermal kettle, the high-pressure hydrothermal kettle is sealed, and placed in an electric heating drying oven for reaction; S4, the product obtained after hydrothermal treatment is calcined in a muffle furnace at a certain temperature to remove the template, thereby obtaining a platinum-based encapsulated mesoporous titanium oxide electrocatalyst.
3. The method of claim 2, wherein the method further comprises: In step S1, the organic solvent is tetrahydrofuran, and the metal precursor is hydrated platinum chloride; in step S2, the evaporation temperature is 30-50 °C, and the evaporation time is 20-26 h; in step S3, the hydrothermal temperature is 60-80 °C, and the hydrothermal time is 20-26 h; in step S4, the calcination temperature is 400-450 °C, the temperature rising program is 1-2 °C / min, and the calcination time is 2-4 h.
4. The method of claim 2, wherein the method further comprises: The non-ionic surfactant is a triblock copolymer, polyethylene glycol-polypropylene glycol-polyethylene glycol, and the triblock copolymer is one of Pluronic P65, Pluronic F108, and Pluronic P123.
5. A platinum-based encapsulated mesoporous titania electrocatalyst prepared according to the method of any one of claims 1-4, characterized in that, It has a spherical morphology, a radial mesoporous structure with a central divergence, a pore size of 9-12 nm, and a Pt single atom / sub-nanocluster loading.
6. The platinum-based encapsulated mesoporous titanium oxide electrocatalyst of claim 5 is used as an acidic cathode catalyst material for electrocatalytic water splitting for hydrogen production.
7. Use of a platinum-based encapsulated mesoporous titania electrocatalyst according to claim 6, characterized in that: The platinum-based encapsulated mesoporous titanium oxide electrocatalyst material is mixed with Nafion solvent and isopropyl alcohol solvent to form a catalyst slurry, and is drop-coated on a rotating disc electrode, and a three-electrode system is used for electrocatalytic application.
8. Use of a platinum-based encapsulated mesoporous titania electrocatalyst according to claim 7, characterized in that, Specifically comprising the following steps: S1 said platinum-based encapsulated mesoporous titanium oxide electrocatalyst material takes 4-6 mg as a catalytically active material; S2 respectively takes 5-20 μL of Nafion solvent, 480-500 μL of isopropyl alcohol solvent and the catalytically active material in S1, and prepares a catalyst slurry by physical mixing; S3 takes 5-20 μL of the above-mentioned catalyst slurry, and drops and coats on the glassy carbon active surface of a rotating disc electrode; after the slurry is dried into a film, it is applied; S4 the rotating disc electrode after the slurry in S3 is dried is used as a working electrode, an Ag / AgCl electrode is used as a reference electrode, a carbon rod is used as a counter electrode, a 1.0 M perchloric acid solution is selected as an electrolyte, a three-electrode system is assembled, and the application of hydrogen production by electrocatalytic water splitting under acidic conditions is carried out.
Citation Information
Patent Citations
Preparation method of mesoporous titanium dioxide ball supported Mn-Ce-W compound oxide denitration catalyst
CN104014331A
Mesoporous P25 titanium dioxide microspheres and preparation method thereof
CN107117649A
Platinum monatomic hydrogen evolution electrocatalyst and preparation method thereof
CN114134532A
Preparation method and hydrogen evolution application of monatomic Pt catalyst
CN114959792A
Platinum-cluster-loaded mesoporous black titanium dioxide nanosheet photocatalyst and preparation method thereof
CN115254097A